Hydrologic error analysis: a lake mass balance as a case study (Emerald Lake - California, usa) - Matteotti, Giovanni (Italian journal of engineering geology and environment, 2009)
The paper describes a methodology taken from theory of errors as a suggestion tool to estimate accuracy in hydrological measurements. First it is introduced the statistical theory underlying most of the cases involving errors of observations that can be divided further on into random, systematic and spurious. Then a methodology taken from the theory of errors suggests how to evaluate global error in a quantity function of more than one variable. This when the single variable uncertainty is evaluated from measurements or else. Also the concept of how errors “propagate” is introduced. The case study is about the Emerald lake basin (California, USA) and deals with its water mass balance including the error term. Focus in on streamflow and evaporation data, that account for most of the total. The suggested method for evaluating uncertainties in measurements is the one step procedure which is more readily applicable and simplify the calculations. The analysis on stream flow and evaporation has exhibited the importance of the right choice of the parameters involved in the mass balance equation. Single uncertainties, since missing large statistical sample to work with, have been assumed, but future work on error analysis will involve the search for rendering data sets closer to the meaning of a significant statistical sample. Total obtained uncertainty is in the order of 10-12% in a good agreement with the values obtained in previous investigations.